Preparation method and application of AlN ceramic product with in-situ converted AlN coating
By preparing an aluminum oxide porous skeleton on the surface of the aluminum substrate and generating the Aln ceramic layer in situ, the problem of high sintering temperature and high cost in the existing Aln ceramic substrate preparation method, and realized low -cost and high -performance Aln ceramic products preparation Essence
Patent Information
- Application Number
- CN202411452416.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing methods for preparing AlN ceramic substrates have problems of high sintering temperature and high cost, and it is difficult to meet the needs of high power electronic packaging.
The method of transforming ALN coating in situ is used to prepare aluminum porous skeleton on the surface of the aluminum substrate, and heated the reaction in the atmosphere of N2 to generate the ALN ceramic layer in situ to reduce the sintering temperature and cost.
It is possible to obtain AlN ceramic products with high thermal conductivity and high electrical insulation under low-cost and low reaction temperature conditions, which are suitable for substrate materials for ultra-high-speed and large-chip integrated circuit packaging.
Smart Images

Figure CN119330721A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of aluminum substrate surface treatment and preparation of metal-based composite materials, and in particular to a preparation method and application of an AlN ceramic product with an in-situ converted AlN coating. Background Art
[0002] In recent years, packaging materials and technologies have become a research hotspot in the microelectronics industry. Although Al2O3 ceramic plates are still the most widely used electronic packaging ceramic materials, with the rapid development of the computer industry, the integration and chip area are getting larger and larger, the speed is getting faster and faster, and the power is constantly increasing. Its shortcomings of low thermal conductivity, high dielectric constant and large mismatch with the chip thermal expansion coefficient are becoming increasingly prominent, and it can no longer meet the needs of future high-power electronic development. AlN ceramic plates have attracted widespread attention due to their much higher thermal conductivity than Al2O3 ceramic plates and thermal expansion coefficients similar to Si. They have been regarded as the most promising substrate material in high-density and high-power electronic packaging.
[0003] At present, the preparation of AlN ceramic substrates usually requires high-temperature sintering, and the sintering temperature reaches 1800℃ or even higher, resulting in high processing costs. Directly preparing AlN ceramics on the surface of aluminum alloys seems to be an effective way to solve the high sintering temperature. Patent CN102912286B puts the preheated aluminum workpiece into a molten bath salt for nitriding at a temperature of 580-610℃ for 1-5h; Patent CN102943230B involves a surface nitriding method for aluminum alloys, which mainly includes nitriding treatment (580-640℃, 10-50 hours) after removing the surface oxide film to obtain a nitrided layer. The above patents perform nitriding treatment on the surface of aluminum workpieces. According to research, there has never been a patent or literature report on the in-situ preparation of AlN ceramics directly on aluminum products. Therefore, the present invention innovatively proposes a method for in-situ preparation of AlN ceramic substrates on aluminum substrates, which is expected to become an ideal substrate material for ultra-high-speed and large-chip integrated circuit packaging. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of high sintering temperature and high cost in the existing method for preparing AlN ceramic substrates, and to provide a preparation method and application of AlN ceramic products with in-situ conversion AlN coatings.
[0005] A method for preparing an AlN ceramic product with an in-situ conversion AlN coating is specifically completed by the following steps:
[0006] 1. Preprocessing:
[0007] Removing impurities and oil stains on the surface of the aluminum substrate to obtain a pretreated aluminum substrate;
[0008] 2. Preparation of porous alumina skeleton:
[0009] A porous aluminum oxide layer is prepared on the surface of the pretreated aluminum substrate by using a micro-arc plasma discharge oxidation technology to obtain an aluminum substrate with a porous aluminum oxide skeleton on the surface;
[0010] 3. Preparation of aluminum-based composite materials:
[0011] An aluminum substrate with a porous alumina skeleton on its surface is placed in an atmosphere furnace with N2, and the atmosphere furnace is heated to a reaction temperature. At the reaction temperature, N2 passes through the holes in the porous alumina skeleton and reacts with the internal aluminum to generate AlN in situ, wherein the porous outer layer of alumina serves as a skeleton to support the internal aluminum substrate. After keeping the temperature for a period of time, an AlN ceramic product with an in-situ converted AlN coating is obtained.
[0012] Principle of the present invention:
[0013] The purpose of selecting aluminum foil, aluminum wire, and thin aluminum plate in the present invention is to reduce the risk of deformation and collapse of the melted structure due to the thickness of the aluminum product during the synthesis of AlN ceramics through N2 reaction, thereby making it difficult to form an AlN ceramic layer with a complete structure. The purpose of further using micro-arc plasma oxidation technology to prepare an alumina porous skeleton on the surface of the pretreated substrate is to ① maintain a high porosity (including through holes) to ensure that N2 is fully in contact with the internal aluminum product during the sintering process so that it fully reacts to form AlN; ②, to obtain an alumina porous skeleton to support the aluminum product, maintain its mechanical bearing capacity during the reaction to form AlN at 700-900°C in a furnace with N2 atmosphere, and prevent it from deforming and collapsing due to high-temperature melting. Finally, the aluminum product with the alumina porous skeleton is heated in an atmosphere furnace with N2 to prepare an AlN ceramic product with a complete structure, which has high thermal conductivity and high electrical insulation properties.
[0014] Advantages of the present invention:
[0015] The present invention obtains an AlN ceramic product with high thermal conductivity and high electrical insulation on the aluminum surface at low cost and lower reaction temperature, which is of great significance to the development of ultra-high speed and large chip integrated circuit packaging substrate materials in my country. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the XRD diagram of the AlN ceramic product prepared on the surface of the aluminum foil in Example 1 of the present invention;
[0017] Figure 2 This is a SEM image of an AlN ceramic product prepared on the surface of an aluminum foil in Example 1 of the present invention;
[0018] Figure 3 This is a schematic diagram of the structure of preparing an AlN ceramic product on the surface of an aluminum foil in Example 1 of the present invention;
[0019] Figure 4 The macroscopic images of AlN ceramic products prepared on the surfaces of aluminum foil, aluminum wire and aluminum plate in Example 1 of the present invention are shown;
[0020] Figure 5 The electrical insulation performance diagram of AlN ceramic products prepared on the surfaces of aluminum foil and aluminum plate in Example 1 of the present invention;
[0021] Figure 6 This is a graph showing the thermal conductivity performance of AlN ceramic products prepared in different embodiments of the present invention. DETAILED DESCRIPTION
[0022] Specific implementation method 1: This implementation method is a method for preparing an AlN ceramic product with an in-situ conversion AlN coating, which is specifically completed in the following steps:
[0023] 1. Preprocessing:
[0024] Removing impurities and oil stains on the surface of the aluminum substrate to obtain a pretreated aluminum substrate;
[0025] 2. Preparation of porous alumina skeleton:
[0026] A porous aluminum oxide layer is prepared on the surface of the pretreated aluminum substrate by using a micro-arc plasma discharge oxidation technology to obtain an aluminum substrate with a porous aluminum oxide skeleton on the surface;
[0027] 3. Preparation of aluminum-based composite materials:
[0028] An aluminum substrate with a porous alumina skeleton on its surface is placed in an atmosphere furnace with N2, and the atmosphere furnace is heated to a reaction temperature. At the reaction temperature, N2 passes through the holes in the porous alumina skeleton and reacts with the internal aluminum to generate AlN in situ, wherein the porous outer layer of alumina serves as a skeleton to support the internal aluminum substrate. After keeping the temperature for a period of time, an AlN ceramic product with an in-situ converted AlN coating is obtained.
[0029] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the aluminum substrate described in step 1 is aluminum foil, aluminum wire or aluminum plate. The other steps are the same as those in specific implementation method 1.
[0030] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that: the specific method of preparing a porous aluminum oxide layer on the surface of the pretreated aluminum substrate using micro-arc plasma discharge oxidation technology in step two is: first, immerse the pretreated aluminum substrate in a stainless steel electrolytic cell filled with electrolyte, then connect the pretreated aluminum substrate to the positive electrode of the power supply, connect the stainless steel electrolytic cell to the negative electrode of the power supply, and oxidize for a period of time under the conditions of electrolyte temperature of 10°C to 50°C, applied voltage of 250V to 400V, frequency of 200Hz to 1000Hz and duty cycle of 4% to 30%, to construct an aluminum oxide porous skeleton with a through-hole structure. The other steps are the same as those of specific implementation method one or two.
[0031] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the oxidation time is 2 minutes to 10 minutes. The other steps are the same as those of specific embodiments 1 to 3.
[0032] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the electrolyte is composed of sodium silicate, sodium phosphate, sodium hydroxide and water; the concentration of sodium silicate in the electrolyte is 1g / L to 20g / L, the concentration of sodium phosphate is 1g / L to 40g / L, and the concentration of sodium hydroxide is 1g / L to 20g / L. The other steps are the same as those of specific embodiments 1 to 4.
[0033] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the thickness of the porous alumina skeleton in step 2 is 3 μm to 15 μm, and the porosity is 20% to 70%. The other steps are the same as those in specific implementation examples 1 to 5.
[0034] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the pressure of the N2 atmosphere furnace described in step 3 is 0.1 MPa, and the purity of N2 is 99.99%; the N2 atmosphere furnace described in step 3 needs to be filled with nitrogen for 1h to 2h before heating. The other steps are the same as those of specific embodiments 1 to 6.
[0035] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the reaction temperature in step 3 is 700° C. to 900° C. The other steps are the same as those in specific embodiments 1 to 7.
[0036] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the heating rate in step 3 is 5°C / min to 10°C / min; the insulation time in step 3 is 10min to 40min. The other steps are the same as those in specific embodiments 1 to 8.
[0037] Specific implementation method ten: This implementation method is an aluminum-based composite material with an in-situ conversion AlN coating and is used in the field of high thermal conductivity and high insulation electronic packaging.
[0038] The following examples are used to verify the beneficial effects of the present invention:
[0039] Embodiment 1: A method for preparing an aluminum-based composite material with an in-situ conversion AlN coating is specifically completed by the following steps:
[0040] 1. Preprocessing:
[0041] The surface of the aluminum substrate was polished using 800#, 1000# and 1200# sandpapers in sequence, and then ultrasonically cleaned using anhydrous ethanol and deionized water for 30 minutes respectively to remove impurities and oxide layers on the surface, thereby obtaining a pretreated aluminum substrate;
[0042] The aluminum substrate described in step 1 is aluminum foil, aluminum wire or aluminum plate;
[0043] 2. Preparation of porous alumina skeleton:
[0044] A porous aluminum oxide layer is prepared on the surface of the pretreated aluminum substrate by using a micro-arc plasma discharge oxidation technology to obtain an aluminum substrate with a porous aluminum oxide skeleton on the surface;
[0045] The specific method of preparing a porous aluminum oxide layer on the surface of the pretreated aluminum substrate by using micro-arc plasma discharge oxidation technology in step 2 is as follows: first, immersing the pretreated aluminum substrate in a stainless steel electrolytic cell filled with an electrolyte, and then connecting the pretreated aluminum substrate to the positive electrode of the power supply, connecting the stainless steel electrolytic cell to the negative electrode of the power supply, and oxidizing for 4 minutes under the conditions of an electrolyte temperature of 25° C., a pulse voltage of 250V applied to both ends of the electrolytic cell, a frequency of 400Hz, and a duty cycle of 4%, to construct an aluminum oxide porous skeleton with a through-hole structure;
[0046] The electrolyte is composed of sodium silicate, sodium phosphate, sodium hydroxide and water; the concentration of sodium silicate in the electrolyte is 15g / L, the concentration of sodium phosphate is 20g / L, and the concentration of sodium hydroxide is 5g / L;
[0047] The thickness of the alumina porous skeleton described in step 2 is 8 μm and the porosity is 50%;
[0048] 3. Preparation of aluminum-based composite materials:
[0049] An aluminum substrate with a porous aluminum oxide skeleton on the surface is placed in an atmosphere furnace with N2, and the atmosphere furnace is heated to 750°C at a heating rate of 5°C / min. At 750°C, N2 passes through the holes in the porous aluminum oxide skeleton and reacts with the internal aluminum to generate AlN in situ, wherein the porous outer layer of the aluminum oxide serves as a skeleton to support the internal aluminum substrate. The aluminum substrate is kept warm for 20 minutes to obtain an aluminum-based composite material (AlN ceramic product) with an in-situ conversion AlN coating.
[0050] The gas pressure of the N2 atmosphere furnace described in step 3 is 0.1 MPa, and the purity of N2 is 99.99%;
[0051] The N2 atmosphere furnace described in step 3 needs to be filled with nitrogen for 1 hour before heating.
[0052] Figure 1 XRD analysis of AlN ceramic products prepared on the surface of aluminum foil is shown in Figure 1 As shown;
[0053] Figure 1 This is the XRD diagram of the AlN ceramic product prepared on the surface of the aluminum foil in Example 1 of the present invention;
[0054] Figure 1 The results show that in addition to the diffraction peaks of Al and Al2O3, there are a large number of diffraction peaks of AlN in the product, proving that this technology can form an AlN ceramic layer on the surface of aluminum and its alloy products.
[0055] Figure 2 This is a SEM image of an AlN ceramic product prepared on the surface of an aluminum foil in Example 1 of the present invention;
[0056] like Figure 2 As shown in the figure, the surface scanning morphology shows that the surface of the AlN ceramic product presents a ceramic structure morphology formed by the reaction of aluminum and nitrogen, which further proves that N2 can enter through the through holes in the porous skeleton of alumina and react with the internal aluminum to form AlN. The AlN sintered dense ceramic layer can be clearly observed, indicating that the AlN substrate can be successfully prepared at low temperature.
[0057] Figure 3 This is a schematic diagram of the structure of preparing an AlN ceramic product on the surface of an aluminum foil in Example 1 of the present invention;
[0058] like Figure 3 As shown, an AlN ceramic product can be prepared by placing an aluminum substrate with an alumina porous skeleton in a furnace with a N2 atmosphere, wherein the Al in the aluminum substrate flows into the alumina porous skeleton at a high temperature and reacts with N2 to form an AlN and Al2O3 composite structure, and the aluminum substrate itself also reacts with N2 to form an AlN layer, and finally an AlN ceramic product with an AlN coating is prepared ( Figure 3 ).
[0059] Figure 4 The macroscopic images of AlN ceramic products prepared on the surfaces of aluminum foil, aluminum wire and aluminum plate in Example 1 of the present invention are shown;
[0060] from Figure 4 It can be seen that the surface of the product is grayish white; while the coating prepared on the aluminum substrate using the micro-arc plasma oxidation technology in the above-mentioned electrolyte system is white, which is attributed to the fact that the main phase of the micro-arc plasma oxidation coating is the Al2O3 phase. Therefore, the macroscopic morphology further proves that AlN ceramic products have been successfully prepared on the surface of aluminum and its alloys using this technology. At the same time, it can be clearly observed that both aluminum foil, aluminum wire and aluminum plate show good structural integrity, without structural deformation and collapse, proving that AlN ceramic products with complete structure have been prepared.
[0061] Figure 5 The electrical insulation performance diagram of AlN ceramic products prepared on the surfaces of aluminum foil and aluminum plate in Example 1 of the present invention;
[0062] from Figure 5 It can be seen that the aluminum alloy products with AlN ceramic layer have excellent electrical insulation properties, with a withstand voltage of more than 1000V and a resistance value greater than 100MΩ.
[0063] The thermal conductivity performance diagram of the AlN ceramic product prepared in Example 1 is shown in Figure 6 As shown;
[0064] The AlN ceramic product prepared in Example 1 has a high thermal conductivity of 190 W / mK and can be used as a substrate with high thermal conductivity, high insulation and high heat dissipation.
[0065] Embodiment 2: A method for preparing an aluminum-based composite material with an in-situ conversion AlN coating is specifically completed by the following steps:
[0066] 1. Preprocessing:
[0067] The surface of the aluminum substrate was polished using 800#, 1000# and 1200# sandpapers in sequence, and then ultrasonically cleaned using anhydrous ethanol and deionized water for 30 minutes respectively to remove impurities and oxide layers on the surface, thereby obtaining a pretreated aluminum substrate;
[0068] The aluminum substrate described in step 1 is aluminum foil, aluminum wire or aluminum plate;
[0069] 2. Preparation of porous alumina skeleton:
[0070] A porous aluminum oxide layer is prepared on the surface of the pretreated aluminum substrate by using a micro-arc plasma discharge oxidation technology to obtain an aluminum substrate with a porous aluminum oxide skeleton on the surface;
[0071] The specific method of preparing a porous aluminum oxide layer on the surface of the pretreated aluminum substrate by using micro-arc plasma discharge oxidation technology in step 2 is as follows: first, immersing the pretreated aluminum substrate in a stainless steel electrolytic cell filled with an electrolyte, and then connecting the pretreated aluminum substrate to the positive electrode of the power supply, connecting the stainless steel electrolytic cell to the negative electrode of the power supply, and oxidizing for 7 minutes under the conditions of an electrolyte temperature of 35° C., a pulse voltage of 300V applied to both ends of the electrolytic cell, a frequency of 600 Hz, and a duty cycle of 6%, to construct an aluminum oxide porous skeleton with a through-hole structure;
[0072] The electrolyte is composed of sodium silicate, sodium phosphate, sodium hydroxide and water; the concentration of sodium silicate in the electrolyte is 20g / L, the concentration of sodium phosphate is 10g / L, and the concentration of sodium hydroxide is 4g / L;
[0073] The thickness of the porous alumina skeleton described in step 2 is 11 μm and the porosity is 42%;
[0074] 3. Preparation of aluminum-based composite materials:
[0075] An aluminum substrate with a porous aluminum oxide skeleton on the surface is placed in an atmosphere furnace with N2, and the atmosphere furnace is heated to 800°C at a heating rate of 5°C / min. At 800°C, N2 passes through the holes in the porous aluminum oxide skeleton and reacts with the internal aluminum to generate AlN in situ, wherein the porous outer layer of the aluminum oxide serves as a skeleton to support the internal aluminum substrate. The aluminum substrate is kept warm for 15 minutes to obtain an aluminum-based composite material (AlN ceramic product) with an in-situ conversion AlN coating.
[0076] The gas pressure of the N2 atmosphere furnace described in step 3 is 0.1 MPa, and the purity of N2 is 99.99%;
[0077] The N2 atmosphere furnace described in step 3 needs to be filled with nitrogen for 1 hour before heating.
[0078] The electrical insulation properties of the AlN coating prepared on the surface of the aluminum foil and the aluminum plate in Example 2 are shown in Table 1; the insulation resistance of the AlN coating on the surface of the aluminum foil is 152MΩ and the breakdown voltage is above 1300V; the insulation resistance of the AlN coating on the surface of the aluminum plate is 159MΩ and the breakdown voltage is above 1371V.
[0079] The thermal conductivity performance diagram of the AlN ceramic product prepared in Example 2 is shown in Figure 6 As shown;
[0080] The AlN ceramic product prepared in Example 2 has a high thermal conductivity of 193 W / mK and can be used as a substrate with high thermal conductivity, high insulation and high heat dissipation.
[0081] Embodiment 3: A method for preparing an aluminum-based composite material with an in-situ conversion AlN coating is specifically completed by the following steps:
[0082] 1. Preprocessing:
[0083] The surface of the aluminum substrate was polished using 800#, 1000# and 1200# sandpapers in sequence, and then ultrasonically cleaned using anhydrous ethanol and deionized water for 30 minutes respectively to remove impurities and oxide layers on the surface, thereby obtaining a pretreated aluminum substrate;
[0084] The aluminum substrate described in step 1 is aluminum foil, aluminum wire or aluminum plate;
[0085] 2. Preparation of porous alumina skeleton:
[0086] A porous aluminum oxide layer is prepared on the surface of the pretreated aluminum substrate by using a micro-arc plasma discharge oxidation technology to obtain an aluminum substrate with a porous aluminum oxide skeleton on the surface;
[0087] The specific method of preparing a porous aluminum oxide layer on the surface of the pretreated aluminum substrate by using micro-arc plasma discharge oxidation technology in step 2 is as follows: first, immersing the pretreated aluminum substrate in a stainless steel electrolytic cell filled with an electrolyte, and then connecting the pretreated aluminum substrate to the positive electrode of the power supply, connecting the stainless steel electrolytic cell to the negative electrode of the power supply, and oxidizing for 8 minutes under the conditions of an electrolyte temperature of 45° C., a pulse voltage of 300V applied to both ends of the electrolytic cell, a frequency of 300 Hz, and a duty cycle of 20%, to construct an aluminum oxide porous skeleton with a through-hole structure;
[0088] The electrolyte is composed of sodium silicate, sodium phosphate, sodium hydroxide and water; the concentration of sodium silicate in the electrolyte is 10g / L, the concentration of sodium phosphate is 30g / L, and the concentration of sodium hydroxide is 5g / L;
[0089] The thickness of the porous alumina skeleton described in step 2 is 12 μm and the porosity is 51%;
[0090] 3. Preparation of aluminum-based composite materials:
[0091] An aluminum substrate with a porous aluminum oxide skeleton on the surface is placed in an atmosphere furnace with N2, and the atmosphere furnace is heated to 900°C at a heating rate of 5°C / min. At 900°C, N2 passes through the holes in the porous aluminum oxide skeleton and reacts with the internal aluminum to generate AlN in situ, wherein the porous outer layer of the aluminum oxide serves as a skeleton to support the internal aluminum substrate. The aluminum substrate is kept warm for 30 minutes to obtain an aluminum-based composite material (AlN ceramic product) with an in-situ conversion AlN coating.
[0092] The gas pressure of the N2 atmosphere furnace described in step 3 is 0.1 MPa, and the purity of N2 is 99.99%;
[0093] The N2 atmosphere furnace described in step 3 needs to be filled with nitrogen for 1 hour before heating.
[0094] The electrical insulation properties of the AlN coating prepared on the surface of the aluminum foil and the aluminum plate in Example 3 are shown in Table 1; the insulation resistance of the AlN coating on the surface of the aluminum foil is 161MΩ and the breakdown voltage is above 1376V; the insulation resistance of the AlN coating on the surface of the aluminum plate is 178MΩ and the breakdown voltage is above 1405V.
[0095] Table 1 Electrical insulation properties of Example 2 and Example 3
[0096]
[0097]
[0098] The thermal conductivity performance diagram of the AlN ceramic product prepared in Example 3 is shown in Figure 6 As shown;
[0099] The AlN ceramic product prepared in Example 3 has a high thermal conductivity of 195 W / mK and can be used as a substrate with high thermal conductivity, high insulation and high heat dissipation.
Claims
1. A method for preparing an AlN ceramic product with an in-situ conversion AlN coating, characterized in that The preparation method is specifically completed according to the following steps:
1. Preprocessing: Removing impurities and oil stains on the surface of the aluminum substrate to obtain a pretreated aluminum substrate; 2. Preparation of porous alumina skeleton: A porous aluminum oxide layer is prepared on the surface of the pretreated aluminum substrate by using a micro-arc plasma discharge oxidation technology to obtain an aluminum substrate with a porous aluminum oxide skeleton on the surface; 3. Preparation of aluminum-based composite materials: An aluminum substrate with a porous alumina skeleton on its surface is placed in an atmosphere furnace with N2, and the atmosphere furnace is heated to a reaction temperature. At the reaction temperature, N2 passes through the holes in the porous alumina skeleton and reacts with the internal aluminum to generate AlN in situ, wherein the porous outer layer of alumina serves as a skeleton to support the internal aluminum substrate. After keeping the temperature for a period of time, an AlN ceramic product with an in-situ converted AlN coating is obtained.
2. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 1, characterized in that The aluminum substrate described in step 1 is aluminum foil, aluminum wire or aluminum plate.
3. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 1, characterized in that The specific method of preparing a porous alumina layer on the surface of the pretreated aluminum substrate using micro-arc plasma discharge oxidation technology in step 2 is: first, immerse the pretreated aluminum substrate in a stainless steel electrolytic cell filled with electrolyte, and then connect the pretreated aluminum substrate to the positive electrode of the power supply, connect the stainless steel electrolytic cell to the negative electrode of the power supply, and oxidize for a period of time under the conditions of electrolyte temperature of 10°C to 50°C, applied voltage of 250V to 400V, frequency of 200Hz to 1000Hz and duty cycle of 4% to 30% to construct an alumina porous skeleton with a through-hole structure.
4. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 3, characterized in that The oxidation time is 2 minutes to 10 minutes.
5. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 3, characterized in that The electrolyte consists of sodium silicate, sodium phosphate, sodium hydroxide and water; the concentration of sodium silicate in the electrolyte is 1g / L-20g / L, the concentration of sodium phosphate is 1g / L-40g / L, and the concentration of sodium hydroxide is 1g / L-20g / L.
6. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 1, characterized in that The thickness of the alumina porous skeleton described in step 2 is 3 μm to 15 μm, and the porosity is 20% to 70%.
7. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 1, characterized in that The gas pressure of the N2 atmosphere furnace described in step 3 is 0.1 MPa, and the purity of N2 is 99.99%; the N2 atmosphere furnace described in step 3 needs to be filled with nitrogen for 1 h to 2 h before heating.
8. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 1, characterized in that The reaction temperature described in step 3 is 700°C to 900°C.
9. The method for preparing an AlN ceramic product with an in-situ conversion AlN coating according to claim 1, characterized in that The heating rate in step 3 is 5°C / min to 10°C / min; the insulation time in step 3 is 10min to 40min.
10. Application of an AlN ceramic product with an in-situ conversion AlN coating prepared by the preparation method according to claim 1, characterized in that An aluminum-based composite material with an in-situ converted AlN coating is used in the field of high thermal conductivity and high insulation electronic packaging.
Citation Information
Patent Citations
Method for improving corrosion resistance of aluminum-alloy micro-arc oxidation film
CN102409380A
Aluminum oxide / aluminum micro-laminated composite material and preparation method thereof
CN106584963A
Preparation method and application of aluminum nitride porous structural body
CN113248262A
Method for manufacturing aluminum nitride formed body
JP2002068842A
Chamber of plasma system, liner for plasma system and method for installing liner to plasma system
US20170256383A1